Joint and muscle injuries in men and women CrossFit® training participants. Issue 3 (4th May 2022) - Toledo, Ramon; Dias, Marcelo Ricardo; Souza, Daniel; Soares, Raphael; Toledo, Ronam; Lácio, Marcio; Vianna, Jeferson
ABSTRACT: Objective: Verify the incidence and rate of joint and muscle injuries with the practice of CrossFit® and the potential risk factors for injuries in men and women. Methods: A total of 184 CrossFit® participants (97 men and 87 women). A questionnaire was conducted based on characterization, training routine, injuries, and additional information. The incidence refers to the number of new cases of injury in the sample during the CrossFit® training. The injury rate was calculated by estimating the number of weekly training hours and converted into the number of injuries per 1000 training hours. Results: Among the participants, 38.6% reported some type of injury, being joint injuries (83.1%) and/or muscle injuries (45.1%). The injury rate was 3.4/1000 h, with men having a higher rate. The location of the joint injuries was shoulders, wrists, and elbows, in addition to the lumbar spine in women. As for muscle injuries, the deltoid, upper back muscles, and quadriceps femoris were the most reported in men and deltoid, trapezius, upper back muscles, and gastrocnemius in women. Conclusions: A better understanding of the anatomical distribution of the injuries may help coaches prescribe the most adequate workout that may reduce the likelihood of injuries occurring in CrossFit® training participants. It was demonstrated that gender, experience, weekly frequency, and previous injuries are important factors, and professionals must be concerned with the assessment of the participants and with an individualized progression in order to avoid risks.